Simple Verifiable Elections - Benaloh, Josh (Proceedings of the 2006 Electronic Voting Technology Workshop, 2006)
Much work has been done in recent decades to apply sophisticated cryptographic techniques to achieve strong end-to-end verifiability in election protocols. The properties of these protocols are much stronger than in any system in general use; however, the complexity of these systems has retarded their adoption. This paper describes a relatively simple but still effective approach to cryptographic elections. Although not as computationally efficient as previously proposed cryptographic approaches, the work presented herein is intended to be more accessible and therefore more suitable for comparison with other voting systems.